The Effectiveness Of Poster Comment Method In Teaching Writing Recount Text - Muhammad Edy Thoyib; Harizatul Aziziyah (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Writing skill is very important in the current era, yet writing is one of the most challenging skills to master. Consequently, the Teacher should be innovative in teaching writing in the English learning process for their students. This research aims to find out the effectiveness of Poster Comment in increasing students